(untitled) (Medico Legal Update, 2021)
Background: Premature ovarian insufficiency (POI) is a delicate medical problem in young women. This condition is not unchangeable and permanent but is associated with intermittent and unpredictable ovarian activity, resulting in low conception rate. Over the period of 8 years, the evaluation of secondary amenorrhea was conducted in 90 patients below the age of 40 who wished to restore fertility and is characterized by irregular or absent periods and reduced fertility. Symptoms include those associated with the natural menopause (night sweats and vaginal dryness), and with the long-term adverse effects of estrogen deficiency (osteoporosis and cardiovascular disease): The latter is believed to explain the shorter life expectancy associated with POI. Aim: To illustrate the predictive value of progesterone receptors (PRs), estrogen receptors (ERs), progesterone (PRG), estradiol (E2), Lulilizing hormones (LH), Follicle stimulating hormones (FSH) and Anti mullerian hormones (AMH) serum levels as diagnostic approach for POI. Method: Sixty (60) women with idiopathic POF with thirty (30) women as control groups were included in the study. Baseline investigation in all subjects included serum progesterone receptors(PRs), estrogen receptors(ERs), progesterone (PRG), estradiol (E2), Lulilizing hormones (LH), Follicle stimulating hormones (FSH) and Anti mullerian hormones (AMH) levels were estimated using appropriate assays in biochemistry laboratory. Results: There was statistically significant differences in the serum progesterone receptors, estrogen receptors, progesterone, estradiol, LH, FSH and AMH in POI cases when compared with healthy control (P=<0.05). Conclusion: These results indicate that serum progesterone and estrogen receptors levels, is high in POI cases as a result of lack progesterone and estradiol hormones as a result of loss negative feedback inhibition,this result may be used to primary diagnosis of premature ovarian failure.